Psychosocial Health: Hidden Effects in the Water Supply and Sanitation Environment - Ira Kusumawaty; Ari Siswanto (Program Pascasarjana Universitas Sriwijaya, 2021)
The conceptualization of water and sanitation as the foundation of life is the key to the success of sustainable development in the health sector. Fulfilling water and sanitation needs often encounters obstacles in the environment of certain family groups that touches the complexity of psychosocial health problems. The facts show that attention is often neglected to the impact of inadequate fulfillment of clean water and sanitation on psychosocial health. It is very important to further explore the impact of water availability and sanitation on psychosocial health in order to achieve sustainable health development. This qualitative research was carried out with a phenomenological study approach, involving 5 families living on the riverbank in Palembang, South Sumatera Province. The in-depth interview method is carried out until it reaches data saturation, observation and field notes are carried out during the data collection process. The results of data collection were analyzed using the Colaizzi method to obtain four themes including: stress due to not getting access to clean water, economic difficulties that cause emotional distress in accessing clean water, compulsion to use available water and inconvenience to use public sanitation facilities. The implication of this research is the need for policies to facilitate certain groups of people to access their needs for clean water and sanitation by paying attention to the psychological aspects of the community. Collaboration of community leaders is needed in accelerating access to clean water and sanitation that is more respectful of community dignity.